2012
DOI: 10.1002/hec.2845
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Medical Care Use in the British Household Panel Survey

Abstract: We explore whether medical care use is persistent over a long panel using 18 waves of the British Household Panel Survey. Of particular interest is high medical care use because a few high users account for a disproportionate amount of use while many individuals use no medical care in a given year. If health is a primary driver of medical care demand, and we control for health, then past medical care use should be uninformative for future use. However, we find that conditional on health, other covariates and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…What we found was consistent with a longitudinal study in Britain that concluded that, ''the conditional probability of high use after experiencing high use may be fundamentally different for individuals over their remaining lifetime''. 4 Moreover, our finding that chronic conditions provided the greatest improvement in model performance is similar to the literature: one study reported that diagnoses of cancer and diabetes were associated with higher expenditures. 1 Another study using Taiwan's NHI data also concluded that adding morbidity trajectories increased the predictive power of the risk adjustment model.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…What we found was consistent with a longitudinal study in Britain that concluded that, ''the conditional probability of high use after experiencing high use may be fundamentally different for individuals over their remaining lifetime''. 4 Moreover, our finding that chronic conditions provided the greatest improvement in model performance is similar to the literature: one study reported that diagnoses of cancer and diabetes were associated with higher expenditures. 1 Another study using Taiwan's NHI data also concluded that adding morbidity trajectories increased the predictive power of the risk adjustment model.…”
Section: Discussionsupporting
confidence: 86%
“…Secondly, despite having 5 years of insurance claims, our data included only one baseline health survey, so we could not use a more advanced dynamic model to control for unobservable heterogeneity. 4 Thirdly, there were some differences between the consent and the nonconsent groups with the latter excluded from our sample, though this is unlikely to have affected our main findings since none of the characteristics on which consenters and non-consenters differed were significant predictors of health care expenditures in our regression analyses.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to the studies of U.S. spending summarized in Table 1, an interesting recent study used an 18-year balanced panel of persons age 16 and over from the British Household Panel Survey to examine the persistence of healthcare utilization (Kohn & Liu, 2013). Key findings were that past use predicted future use even after controlling for health and other characteristics, that past utilization predicted future utilization more strongly at older ages and lower health status, and that first year utilization retained some predictive power throughout the follow-up.…”
Section: Key Prior Studies On Persistence Of Health Spendingmentioning
confidence: 99%